A single exercise session improves side-effects of chemotherapy in women with breast cancer: an observational study - Anna Johnsson; Ingrid Demmelmaier; Katarina Sjövall; Philippe Wagner; Håkan Olsson; Åsa B. Tornberg (BMC Cancer, 2019)
Abstract Background To measure changes in four common chemotherapy related side-effects (low energy, stress, nausea and pain) immediately after a single exercise session within the first week after treatment. Methods Thirty-eight patients with chemotherapy-treated breast cancer, participating in a multi-centre randomised controlled study, the Physical Training and Cancer study (Phys-Can) were included in this sub-study. The Phys-Can intervention included endurance and resistance training. Before and after a single training session (endurance or resistance) within the first week of chemotherapy, energy and stress were measured with the Stress-Energy Questionnaire during Leisure Time, and nausea and pain were assessed using a Visual Analog Scale 0–10. Paired t-tests were performed to analyse the changes, and linear regression was used to analyse associations with potential predictors. Results Thirty-eight participants performed 26 endurance training sessions and 31 resistance training sessions in the first week after chemotherapy. Energy and nausea improved significantly after endurance training, and energy, stress and nausea improved significantly after resistance training. Energy increased (p = 0.03 and 0.001) and nausea decreased (p = 0.006 and 0.034) immediately after a single session of endurance or resistance training, and stress decreased (p = 0.014) after resistance exercise. Conclusions Both endurance and resistance training were followed by an immediate improvement of common chemotherapy-related side-effects in patients with breast cancer. Patients should be encouraged to exercise even if they suffer from fatigue or nausea during chemotherapy. Trial registration NCT02473003, June 16, 2015.